Armed conflicts and kidney patients: a consensus statement from the Renal Disaster Relief Task Force of the ERA - TUĞLULAR, ZÜBEYDE SERHAN (My University, 2022)
During conflicts, people with kidney disease, either those remaining in the affected zones or those who are displaced, may be exposed to additional threats because of medical and logistical challenges. Acute kidney injury developing on the battlefield, in field hospitals or in higher-level hospital settings is characterized by poor outcomes. People with chronic kidney disease may experience treatment interruptions, contributing to worsening kidney function. Patients living on dialysis or with a functioning graft may experience limitations of dialysis possibilities or availability of immunosuppressive medications, increasing the risk of severe complications including death. When patients must flee, these threats are compounded by unhealthy and insecure conditions both during displacement and/or at their destination. Measures to attenuate these risks may only be partially effective. Local preparedness for overall and medical/kidney-related disaster response is essential. Due to limitations in supply, adjustments in dialysis frequency or dose, switching between hemodialysis and peritoneal dialysis and changes in immunosuppressive regimens may be required. Telemedicine (if possible) may be useful to support inexperienced local physicians in managing medical and logistical challenges. Limited treatment possibilities during warfare may necessitate referral of patients to distant higher-level hospitals, once urgent care has been initiated. Preparation for disasters should occur ahead of time. Inclusion of disaster nephrology in medical and nursing curricula and training of patients, families and others on self-care and medical practice in austere settings may enhance awareness and preparedness, support best practices adapted to the demanding circumstances and prepare non-professionals to lend support.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; TRANSPLANTASYON; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; TRANSPLANTATION; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Üroloji; Transplantasyon; Urology; Transplantation; conflicts; dialysis; disasters; kidney patients; wars